Current Treatment Strategies for Obesity Including Indian scenario - Prashar, Deepak (Asian Journal of Pharmaceutics (AJP), 2016)
Aim: The aim of the review is to recapitulate the existing treatment strategies for obesity including Indian scenario. Materials and Methods: The data are extracted from electronic databases and journal search, to find meta-analysis, systematic reviews and randomized, placebo-controlled trials for currently approved obesity medications. The evidence-based surgical and nonsurgical treatments for obesity is studied and evaluated. Results and Discussion: The outcome of the review work put forward the prevalence of nonrationalized treatment strategies for obesity management. Moreover, the review also suggested the current status of the anti-obesity agents in use. Conclusion: The present work concludes that current treatment methodologies are convenient for the treatment and management of obesity. But still, further clinical investigations are required for the proper selection of better treatment. The associated diseases and adverse drug reactions produced by currently used drug therapy plays a vital role in deciding the better curing options